The Influence of Cumulative Grade Point Average and Interest in Continuing to College on the Career Path of Students - Pitaloka, Dea Ayu; Nasution, Toni (Borong Newinera Publisher, 2025)
This research aims to determine the effect of cumulative achievement index and interest on career path among Tadris IPS FITK UINSU students. This research uses a quantitative approach with the es-post facto method, because the data obtained will be expressed in the form of numbers and analyzed based on statistics. This research looks for the independent influence variables of cumulative achievement index (X1) and interest in continuing higher education (X2) and career path (Y). This research was conducted at the Islamic University of North Sumatra, Medan, on Tadris IPS students. The population in this research is 2018 and 2019, including 200 students. The sample collection technique used in this research used a purposive sampling technique, so the sample used in this study was 67 people. Data analysis in this research was carried out quantitatively through 3 stages, namely descriptive analysis, swimmer test analysis, and hypothesis testing. The results of the research show that the cumulative achievement index and interests have a positive effect on the career path of Tadris IPS FITK students at the State Islamic University of North Sumatra Medan as shown by the results of the f test with a significance value of 0.000 < 0.05. So H0 is rejected and Ha is accepted. So it can be concluded that the Cumulative Achievement Index variable, interests simultaneously (together) influence the career path of Tadris IPS FITK students at the State Islamic University of North Sumatra Medan.